THE PERCEPTIONS OF GRADE 10 TEACHERS AND LEARNERS TOWARDS THE USE OF AUGMENTED REALITY (AR) TO TEACH ENGLISH READING COMPREHENSION IN CHRIS HANI WEST DISTRICT, EASTERN CAPE - Ntini, Siyabonga; Nomlala, Lundi (Journal of Ecohumanism, 2026)
This paper examines the perceptions of grade 10 learners and their teachers regarding the use of AR technology in English reading comprehension lessons in the Chris Hani West District. The aim was to examine the perceptions of grade 10 teachers and learners regarding AR on teaching reading practices and learning outcomes, comparing its effectiveness with traditional methods. Guided by an interpretivist paradigm, a case study design was employed, utilizing semi-structured interviews with purposively sampled teachers and learners. Thematic analysis revealed that learners and teachers viewed AR as a pedagogical teaching tool that can significantly enhance learner engagement, motivation, and collaborative learning. Key findings indicate that AR assisted in vocabulary development, improved text visualization, and led to better information retention and comprehension compared to traditional instruction. Both teachers and learners perceived AR as a valuable and innovative pedagogical tool. The study concludes that AR holds significant promise for creating dynamic, learner-centered reading comprehension instruction, thereby contributing to the literature by providing empirical, context-rich evidence from an under-researched FAL setting. Its successful integration, however, is contingent upon adequate teacher training, reliable technical infrastructure, and ongoing support. Recommendations include adopting AR as a supplementary teaching tool, investing in continuous professional development for teachers, and improving school technological resources to facilitate effective implementation.